QUALITY MANAGEMENT PRACTICES IN GONDRANG-PULCHOWK SIX-LANE ROAD UPGRADING PROJECT AT CHITWAN DISTRICT, NEPAL - Pokharel, Aashika; Sharma, Itiza; Lamichhane, Bipana (International Journal of Research -GRANTHAALAYAH, 2023)
The objective of this study is to assess the current quality management practices, determine the factors affecting quality management and to find out remedial measures that will improve the quality management practices in Gondrang-Pulchowk six-lane road construction project. This research methodology is based on interviews and questionnaires survey with clients and contractors who were involved in the project as well as experts from related field. Statistical tools, relative importance index, validity and reliability tests, Spearman’s correlation tests were used for the ranking of different quality aspects. From the comparative study, it was found that most guidelines of the General Conditions of Contract, Special Specifications and Quality Assurance Plan of the contract document were met during project execution although few concerns of safety and correspondence remain to be addressed. From the questionnaire survey, it was found that the practices to achieve quality need to be improved. Contractors consider cost factors as major factor affecting quality in the project whereas lack of supervision by contractors is cited by the clients as major factor affecting quality. To overcome the challenges of quality, proper material selection and usage, inspection, quality training, setting up quality department are seen as remedial measures. Improving safety at site, maintaining written correspondence, incorporating elements of ISO, proper selection and usage of materials, holding quality trainings and setting up quality control department are recommended for this project.